Genetic variability, correlation and path co-efficients analyses of selected maize (Zea mays L.) genotypes - Roy, Pallabi Rani; Haque, Md Ashraful; Ferdausi, Aleya; Bari, Md Abdullah Al (Fundamental and Applied Agriculture, 2018)
Twenty-five maize genotypes were evaluated to study the genetic variability, correlations and path co-efficient analyses for yield and yield contributing characters. Analysis of variance for sixteen yield contributing traits showed highly significant variations among the genotypes. The estimates of genetic components for the yield contributing traits showed higher phenotypic co- efficient of variation than genotypic co-efficient of variation indicating more environmental influence on the studied traits. Traits under study showed moderate to high heritability. The highest heritability was observed in 1000 kernel weight (79.79), seed numbers ear−1 exhibited the highest genetic ad- vance (55.45) and shoot lodging (223.07) showed the highest genetic advance in percentage of mean. Thousands kernel weight exhibited the highest significant positive correlation (0.746) with yield per plant followed by husk girth (0.620) and ear length (0.432). The negative correlation with yield per plant was observed for days to anthesis, days to maturity and seed numbers per row. Path co-efficient analysis exhibited that the thousands kernel weight had a maximum positive direct effect on grain yield followed by husk girth and ear length. This experiment revealed that the selection based on thousands kernel weight, husk girth and ear length would increase grain yield for yield improvement in maize. Therefore, the research findings would be useful for the identification and selection of traits for future breeding programs of maize.